"Formalism, Puritanicalism, Traditionalism: Approaches to Islamic Legal Reasoning in the 19th‐Century Russian Empire". (July 2014) - Spannaus, Nathan
Abstract As early as the 1730s, the Russian imperial state sought to incorporate its Muslim subjects into the tsarist bureauacracy, first by co‐opting Muslim legal scholars, and later, beginning in 1788, by placing the whole of the ulama under government control. This led to a marginalization of Islamic legal institutions and a transformation of Islamic legal practice under Russian rule. In the early 19th century, ulama sought ways to adapt Islamic law to these institutional changes, and vibrant debates about the purpose and function of legal theory represented an important part of the religious discourse among these Muslim communities. This paper addresses the approaches of three scholars, Abu Nasr Qursawi (1776–1812), ῾Abd al‐Rahim Utiz‐Imani (1754–1834) and Fath Allah Uriwi (1767–1843), who strongly disagreed regarding issues such as the use of usul and furu῾, the permissibility of ijtihad, and the relationship between the ulama and the community. I argue that while each scholar puts forward a different approach to the law — which I term, respectively, formalism, puritanicalism and traditionalism — each of these positions represents a response to their communities' shifting circumstances under Russian rule and a way for the discursive tradition of Islamic law to continue despite the marginalization of legal institutions.